#### Answer

(1, 4)

#### Work Step by Step

Substitute x = 1 into the first equation and solve for y:
y = 4(1) = 4
Check to see if the solution (1, 4) satisfies the second equation:
-3(1) + 4 = 1
-3 + 4 = 1
1 = 1
The solution is (1, 4)

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

(1, 4)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.